Indirect Pathway Metabolic Engineering Strategies for Enhanced Biosynthesis of Hyaluronic Acid in Engineered Corynebacterium glutamicum - Du, Yan; Cheng, Fangyu; Wang, Miaomiao; Xu, Chunmeng; Yu, Huimin (Frontiers in Bioengineering and Biotechnology, 2021)
1 Hyaluronic acid is composed of alternating D-glucuronic acid and N-acetyl-D-glucosamine, with excellent biocompatibility and water retention capacity. To achieve heterologous biosynthesis of HA, Corynebacterium glutamicum, a safe GRAS (generally recognized as safe) host, was utilized and metabolically engineered previously. In this work, to achieve further enhancement of HA yield, four strategies were proposed and performed separately first, i.e. 1) improvement of glucose uptake via iolR gene knockout, releasing the inhibition of transporter IolT1/IolT2 and glucokinases; 2) intensification of cardiolipin synthesis through overexpression of genes pgsA1/pgsA2/cls involved in cardiolipin synthesis; 3) genome-duly-expression of Vitreoscilla hemoglobin, enhancing HA titer coupled with more ATP and improved NAD+/NADH (＞7.5) ratio; 4) identifying the importance of glutamine for HA synthesis through transcriptome analyses and then enhancing the HA titer via its supplement. After that, we combined different strategies together to further increase the titer of HA. As a result, one of the optimal recombinant strain, Cg-dR-CLS, yielded 32 g/L of HA at 60 h in fed-batch culture, which was increased by 30% compared with that of the starting strain. This high value of HA titer will enable the industrial production of HA via the engineered C. glutamicum.